Evaluation of Systemic Antifungal Use in a Latin American General Care Hospital: A Retrospective Study - Abigail Fallas-Mora; Jose Pablo Díaz-Madriz; Jose Miguel Chaverri-Fernández; Esteban Zavaleta-Monestel (MDPI AG, 2023)
Background: Invasive fungal infections significantly contribute to mortality and morbidity rates. Despite the presence of all four major classes of antifungal medications, it is estimated that these infections result in the death of 1.5 million people each year, and death rates are increasing at an alarming rate. With increasing concerns about the emergence of antifungal resistance, there is a growing consideration in many countries to incorporate antifungal stewardship into existing antimicrobial stewardship programs. This approach aims to address issues hindering the appropriate use of antifungal drugs and to optimize their utilization. Methods: An analytical retrospective study of 48 hospitalized patients was conducted to assess factors related to the use of systemic antifungals and develop and implement an internal protocol to improve its use. Results: All patients with severe comorbidity had SOFA scores linked with a mortality risk of more than 10%. Based on 48 evaluations of antifungal orders, 62.5% were considered appropriate, 14.6% were considered debatable, and 22.9% were considered inappropriate. Infectious disease physicians made most of the prescriptions considered appropriate in this study. Conclusions: Comorbidities and risk factors in patients receiving systemic antifungals can be associated with the development of more serious fungal infections; hence, the implementation of antifungal stewardship as a complement to antimicrobial stewardship programs can help facilitate decision-making when dealing with a suspected case of fungal infection.